2006
DOI: 10.1177/1524839904266799
|View full text |Cite
|
Sign up to set email alerts
|

Salud Para Su Corazón-NCLR: A Comprehensive Promotora Outreach Program to Promote Heart-Healthy Behaviors Among Hispanics

Abstract: This article describes results of year-1 implementation of the Salud Para Su Corazón (Health For Your Heart)-National Council of la Raza (NCLR) promotora (lay health worker) program for promoting heart-healthy behaviors among Latinos. Findings of this community outreach initiative include data from promotora pledges and self-skill behaviors, cardiovascular disease risk factors of Latino families, family heart-health education delivery, and program costs associated with promotora time. Participation included 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 12 publications
3
90
0
Order By: Relevance
“…The partners in this collaboration included the North Carolina Farmworkers Project, a non-profit farmworker and service advocacy organization, and Wake Forest University School of Medicine. Lay health advisors can include individuals who vary in activities and training, but generally are members of a community and serve a natural helping role in that community (Eng et al, 1997;Kegler et al, 2003;Balcázar et al, 2006). The goal of this analysis is to evaluate the effectiveness of the La Familia promotora program in teaching women in farmworker families about pesticide safety and increasing residential pesticide safety behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The partners in this collaboration included the North Carolina Farmworkers Project, a non-profit farmworker and service advocacy organization, and Wake Forest University School of Medicine. Lay health advisors can include individuals who vary in activities and training, but generally are members of a community and serve a natural helping role in that community (Eng et al, 1997;Kegler et al, 2003;Balcázar et al, 2006). The goal of this analysis is to evaluate the effectiveness of the La Familia promotora program in teaching women in farmworker families about pesticide safety and increasing residential pesticide safety behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…These authors determined that the intervention participants were more likely to progress through stages of change than their control counterparts. Balcazar et al (2006) found that funding limited the ability to evaluate the extent to which project activities associated with follow-up, referrals, and community events to promote heart health resulted in improvements in the number of new patients screened and changes in lifestyle behaviors among participants. The 1 year time constraint in this study resulted in process inconsistency and lack of complete and clear data collection.…”
Section: Directions For Research and Practicementioning
confidence: 97%
“…Kim et al (2005) provide a relevant description of LHA recruitment and training, addressing system strengths and challenges in implementing a collaborative outreach program designed to address health disparities in a poor Latino community in Los Angeles. Balcazar et al (2006) provide such an example in their implementation of the Salud Para Su Corazon program for promoting heart-healthy behaviors among Latinos. The authors provide detail on program structure and conceptual framework, the promotora training, the program curriculum as a culturally appropriate health education tool, and the application of the promotora model to the delivery of the curriculum in Latino communities.…”
Section: Directions For Research and Practicementioning
confidence: 98%
“…Although Latino peer education has been notably successful in tackling issues on chronic disease and general health and lifestyle (e.g., Balcazar et al, 2006;Elder et al, 2006;Garvin, Cheadle, Chrisman, Chen, & Brunson, 2004;Townsend, Johns, Shilts, & Farfan-Ramirez, 2006), there is some evidence in the literature to suggest that expert interventionists or nonpeer deliverers (e.g., health care providers, counselors) may be more effective in promoting protective sexual behaviors than trained lay community members (Durantini, Albarracin, Mitchell, Earl, & Gillette, 2006;Herbst et al, 2007). More research is needed, however, to better understand effective delivery methods of sensitive sexual and reproductive health messages to immigrant Latino male populations.…”
Section: Discussionmentioning
confidence: 99%